Prevalence and Associated Factors of Adolescent Obesity among Rural School Adolescents in Nepal: A Cross-Sectional Study - Deekshanta Sitaula; Aarati Dhakal; Nimesh Lageju; Amisha Silwal; Samjhana Kshetri Basnet; Niki Shrestha; B. C. Anup Bikram; Niraj Phoju (Global Health, Epidemiology and Genomics)
Background. Overweight and obesity are major risk factors for chronic diseases and are the leading cause of mortality worldwide. Obesity during adolescence is strongly associated with adulthood obesity leading to increased morbidities and mortality. As a developing country undergoing rapid urbanization, Nepal is in a transitional phase where undernutrition coexists with obesity; however, there is a dearth of literature on the status of adolescent obesity in the rural section of Nepal. The aim of this study was to determine the prevalence of adolescent obesity in a rural district of Nepal and find out its associated factors. Methods. An institution-based cross-sectional study was conducted among the adolescent students studying in classes 8, 9, and 10 in four secondary schools of Gosaikunda rural municipality of Rasuwa district, Nepal. Total enumerative sampling was used, and Global School-based Health Survey (GSHS) standard questionnaires were used in collecting the information. Height and weight measurements were taken, and the body mass index was classified according to Asia-Pacific criteria. The collected data were analyzed using “SPSS” version 22. Logistic regression analysis was used to evaluate the associated factors, and a p value of ≤0.05 was considered statistically significant. Results. Out of 267 adolescents, 14.6% were obese and 14.6% were overweight. Of the female participants, 39.6% were either obese or overweight, while 12.6% of the male adolescents were overweight/obese. Among the total participants, 16.5% were underweight, including 14.0% females and 20.4% males. Female adolescents were about five times (AOR: 5.2, 95% CI (2.5–10.9), p < 0.01) more likely of being overweight/obese than male adolescents. Conclusions. More than one-quarter of the adolescents were found to be obese/overweight, and the prevalence was significantly more among female adolescents. It emphasizes the necessity of school-based programs promoting a healthy lifestyle among students to maintain healthy weight status.